For Your Eyes Only: A Privacy-Preserving Authentication Framework Based on Homomorphic Encryption and Retina Biometrics - David Palma; Pier Luca Montessoro (IEEE Access)
Securing personal information and data has become an imperative challenge, especially after the introduction of legal frameworks, such as, in Europe, the General Data Protection Regulation (GDPR). Traditional authentication methods, such as PINs and passwords, are vulnerable to cyber threats, underscoring the need for more robust biometric systems. These systems offer improved security by accurately verifying a user’s identity, reducing the risk of impersonation. The human retina has demonstrated remarkable reliability as a biometric trait mainly because of its unique and stable patterns, even though the adoption of these systems gives rise to significant concerns regarding the confidentiality of biometric data. This study presents a groundbreaking approach to address these concerns by integrating homomorphic encryption into retina-based authentication. The combination of homomorphic encryption and retina biometrics within the proposed framework offers a comprehensive solution that ensures both privacy and security with no loss in accuracy. The proposed approach mitigates the risks associated with possible unauthorised access and security breaches by keeping the data encrypted throughout the entire procedure. Furthermore, it preserves the individual’s privacy by preventing the exposure of sensitive biometric information. We evaluated the proposed system through extensive experiments and simulations, demonstrating its effectiveness in terms of both security and privacy when the system operates in normal (ideal) and abnormal (under attack) conditions. Experimental results indicate that the combined approach offers robust resistance to various attacks, including replay attacks and data exposure, providing a robust and privacy-centric authentication solution.